Validation of Micro Digital Content Model of Project-Based Learning for Guidance and Counseling Courses in Non-Formal Education - Zen, Ella Faridati; Hotifah, Yuliati; Prihatiningsih, Riskiyana; Saputra, Nur Mega Aris (citeus, 2025)
The research aims to produce a product in the form of a learning device for guidance and counseling courses in non-formal education in the form of micro digital based on project-based learning, which is theoretically accepted through expert testing. The development method uses the ADDIE design, with the procedures of Analysis, Design, Development, Implementation and Evaluation. The trial subjects or product assessors consist of material experts and media experts in the field of guidance and counseling. Data were collected with expert assessment instruments and analyzed using the average technique. The expert assessment of the product by material experts produced an average value of 3.9 on precision and 4.0 on usability. while the media expert assessment produced an attractiveness aspect of 3.8 and ease of use of 3.8. Based on the results of the analysis, it can be concluded that the product is very appropriate, very useful, very interesting and very easy, so it is very suitable for use in guidance and counseling lectures at non-formal education. The limitation of this study is that the product produced has not been tested for effectiveness on student groups, so further research is needed to continue testing the effectiveness of the product.